Single‐Site Molybdenum on Solid Support Materials for Catalytic Hydrogenation of N2‐into‐NH3. Issue 48 (5th November 2018) - Azofra, Luis Miguel; Morlanés, Natalia; Poater, Albert; Samantaray, Manoja K.; Vidjayacoumar, Balamurugan; Albahily, Khalid; Cavallo, Luigi; Basset, Jean‐Marie
Abstract: Very stable in operando and low‐loaded atomic molybdenum on solid‐support materials have been prepared and tested to be catalytically active for N2 ‐into‐NH3 hydrogenation. Ammonia synthesis is reported at atmospheric pressure and 400 °C with NH3 rates of approximately 1.3×10 3 μmol h −1 gMo −1 using a well‐defined Mo‐hydride grafted on silica (SiO2‐700 ). DFT modelling on the reaction mechanism suggests that N2 spontaneously binds on monopodal [(≡Si−O‐)MoH3 ]. Based on calculations, the fourth hydrogenation step involving the release of the first NH3 molecule represents the rate‐limiting step of the whole reaction. The inclusion of cobalt co‐catalyst and an alkali caesium additive impregnated on a mesoporous SBA‐15 support increases the formation of NH3 with rates of circa 3.5×10 3 μmol h −1 gMo −1 under similar operating conditions and maximum yield of 29×10 3 μmol h −1 gMo −1 when the pressure is increased to 30 atm. Abstract : It'll be fixed in a Mo : N2 ‐into‐NH3 conversion is one of the most important processes in the chemical industry. A set of molybdenum on solid support materials catalyse N2 fixation under just atmospheric pressure and only 400 °C. They allow for an in‐depth elucidation of the mechanistic events taking place which is supported by DFT analysis.